Uji farmakodinamik, drug-likeness, farmakokinetik dan interaksi senyawa aktif kayu ular (Strychnos lucida) sebagai inhibitor Plasmodium falciparum secara in silico - Dede Rival Novian; Azra Zahrah Nadhirah Ikhwani; Aji Winarso (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Snakewood’s active compounds have known to be potential as anti-plasmodium by the in-vitro study. However, the inhibition activity mechanism of snakewood active compounds against Plasmodium is not yet known. In this study, we determined the activity of snakewood’s active compounds by in-silico approach. Firstly, We identified the pharmacodynamic properties of snakewood’s active compounds, which are SA1, SA2, SA3, SA4, and SA5. Furthermore, drug-likeness and pharmacokinetic: absorption-distribution-metabolism-excretion (ADME) analyses were also carried out against snakewood’s active compounds to determine the most potential candidate for anti-Plasmodium falciparum drug. Molecular docking analyses using Plasmodium falciparum lactate dehydrogenase (PfLDH) enzyme against the active compounds were undertaken to observe their specific interactions. The result of molecular docking based on binding energy and inhibitory constant showed that SA3 (3-ethoxyacetophenone (C9H10O2)) active compound is the most potential inhibitor of PfLDH than others. It’s caused by the binding energy and inhibitory constant of SA3 lower than the other snakewood’s active compound. Therefore, SA3 can be a potential candidate for the anti-plasmodium agent.